Reading and connecting: using social annotation in online classes - Zhu, Xinran; Chen, Bodong; Avadhanam, Rukmini Manasa; Shui, Hong; Zhang, Raymond Zhuo (Information and learning science, 2020)
Purpose The COVID-19 pandemic has forced many instructors to rapidly shift to online/distance teaching. With a narrow preparation window, many instructors are at a loss of strategies that are both effective in responding to the crisis and compatible with their professional practices. One urgent need in classrooms at all levels is to support social reading of course materials. To fulfill this need, this paper aims to present a systematic literature review on using Web annotation in K-12 and higher education to provide practical and evidence-based recommendations for educators to incorporate social annotation in online teaching. Design/methodology/approach This paper presents a systematic literature review of the use of Web annotation in formal education. The authors reviewed 39 articles that met the inclusion criteria and extracted the following information from each article: level of education, subject area, learning theory, learning activity design, Web annotation technology, research methods and learning outcomes. Studies were further analyzed and synthesized by the genre of learning activity design. Findings The authors identified five types of social annotation activity design: processing domain-specific knowledge, supporting argumentation and inquiry, improving literacy skills, supporting instructor and peer assessment and connecting online learning spaces. In addition, the authors developed practical recommendations on setting pedagogical goals, selecting annotation tools, deciding instructor involvement and developing evaluation strategies. Originality/value This study provides a timely response to online/distance teaching under the COVID-19 pandemic. It is a hope that these identified application areas, in combination with four practical recommendations, would provide pragmatic and evidence-based support for educators to engage learners in reading, learning and connecting.